Using Financial Risk Analysis to Examine Investing Behavior During and After A Crisis, Based on VaR and GARCH Models - Tsangari, Haritini (International Journal of Accounting and Economics Studies, 2025)
The assessment of financial risk provides important information for forecasting and investment decision-making. The purpose of this study is to examine investors’ behavior during and after a financial crisis and how the stock market indexes are affected. Two forecasting techniques, namely Value at Risk (VaR) and Generalized Autoregressive Conditional Heteroskedastic (GARCH) models, are used in a comparison of three European stock market indexes in Germany, Spain, and Ireland. It was especially of interest to examine if investors had incomplete information about the development of the economy and how their actions would affect future returns. The results provide a means for delving deeper into the variables that affect the performance of the stock market and the factors that investors consider when making financial decisions. The findings thus give valuable lessons to be used in relation to behaviors under the regime of uncertainty.